Metatranscriptomic Analysis Reveals Active Bacterial Communities in Diabetic Foot Infections - Heravi, Fatemah Sadeghpour; Zakrzewski, Martha; Vickery, Karen; Malone, Matthew; Hu, Honghua (Frontiers in Microbiology, 2020)
Despite the extended view of the composition of diabetic foot infections (DFIs), little is known about which transcriptionally active bacterial communities are pertinent to infection, and if any differences are associated with increased infection severity. We applied an RNA sequencing approach to analyze the composition, function, and pathogenicity of the active bacterial communities in DFIs. Taxonomic profiling of bacterial transcripts revealed the presence of fourteen bacterial phyla in DFIs. The abundance of the Spiroplasma, Vibrio, and Mycoplasma were significantly different in different infection severities (P<0.05). Mild and severe stages of infections were dominated by Staphylococcus aureus and Porphyromonas asaccharolytica, respectively. A total of 132 metabolic pathways were identified of which ribosome and thiamin being among the most highly transcribed pathways. Moreover, a total of 131 antibiotic resistance genes, primarily involved in the multidrug efflux pumps/exporters were identified. Furthermore, iron acquisition systems (synthesize and regulation of siderophores) and pathways involved in the synthesis and regulation of cell-surface components associated with adhesion, colonization, and movement of bacterial cells were the most common virulence factors. These virulence factors may help bacteria compete for scares resources and survive the host wound proteases. Characterization of transcriptionally active bacterial communities can help to provide an understanding of the role of key pathogens in the development of DFIs. Such information can be clinically useful allowing replacement of DFIs empirical therapy with targeted treatment.